The Impact of Bottom Gillnet Construction on Lobster Catch Quality in Segara Bay District, Bengkulu City, Indonesia - Kholis, Muhammad Natsir; Mz, Novita; Khikmawati, Liya Tri (Journal of Fisheries and Environment, 2024)
Lobster represents one of the most valuable non-fish species with significant economic potential in Bengkulu City, with the first lobster fishermen's association being established in Segara Bay District. This research aims to identify the construction of bottom gillnets used by fishermen, assess their compliance with the Indonesian National Standards (SNI), and evaluate their impact on lobster catches in the waters of Segara Bay, Bengkulu City. The study was conducted from April to June 2020 using a survey method that directly observed and measured bottom gillnets, fishing activities, and catch characteristics across 42 fishing operations. Results indicated that the identified bottom gillnets did not meet SNI specifications. Consequently, the primary lobster catches, dominated by scalloped spiny lobster (Panulirus homarus), accounted for only 31% of the total catch, while by-catch constituted a significantly high proportion at 69%. Additionally, the catch exhibited uneven size distributions with a high proportion of undersized lobster (62%), and the estimated first catch size (7.8 cm) was smaller than the size at first maturity. These findings highlight the urgent need for comprehensive improvements in the bottom gillnet dimension standards in Indonesia.